Epiphytic Plant Communities in the Lowland Dipterocarp Forest, Wanariset, East Kalimantan, Before Forest Fire - T Partomihardjo (Department of Forest Resources Conservation and Ecotourism - IPB University, 1991)
The species richness and abundance of vascular epiphytes in the lowland dipterocarp forest, East Kalimantan is described. Fifty six species of vascular epiphytes have been recorded within a 6 ha plot, comprising 39 genera and 12 families. It was recorded that 387 trees (9.84%) of the total trees of 3933, have supported epiphytes. The epiphytic plant communities within two different habitat showed that the swamp area is poorer than the dry land habitat, both in species richness and abundance. Asplenium nidu and Pandanus epiplyhcus were recorded as the common species in both habitats;while Platyceriunl coronarium tends to occur at crown layer especially in the dry-land habitat.